PERAN KOMUNIKASI ORGANISASI DALAM IMPLEMENTASI ADMINISTRASI PERKANTORAN - Maria Raniliati; Willy Tri Hardianto; Agung Suprojo (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
Abstract: Organizational communication is communication that occurs between individuals within an organization, including both internal and external communication. The importance of communication in any implementation of various activities or work of an organization makes it as a determinant in measuring the effectiveness and efficiency of the organization, indicating whether the organization has managed to achieve a goal that has been determined and agreed in advance, especially in the therm of implementation (execution) of office administration. This study used descriptive quantitative research methods, where the data from the research results in the form of numbers and were analyzed by using statistics. The steps of data collection was through observation, documentation, and questionnaire.The results show conclusions: (1) the analysis of the data shows that the role of organizational communication in the implementation of office administration in Lowokwaru District Office has been running well. It can be seen from the classification of respondents' answers to the table of comparative data analysis is that independent variables (X) of 60% answer good. (2) The implementation of office administration existing in Lowokwaru District Office has been running very well. It can be seen from the results of the respondents' answers on dependent variables (Y) of 70% have a very good response categories. (3) Overall, the role of organizational communication in the implementation of administration office has gone well, so it can be said that the role of organizational communication existing in Lowokwaru District Office is able to support the effectiveness in implementating the administration office. Keywords: Organizational Communication, Administration Implementation